PERLINDUNGAN HUKUM TERHADAP HAK CIPTA ATAS KARYA CIPTA DIGITAL DI INDONESIA - EVELYN ANGELITA P. MANURUNG (PREMISE LAW JURNAL, 2013)
The development of current technology influenced much on the field of Intellectual Property Right. The technology of internet with various easiness not only gave benefit to the copy right but also affected loss which affect on law’s breaking virtually. The digital technology improvement nowadays affected on increasing copy right law breaking in Indonesia, especially the digital copy right. The law protection on copy right which was based on digital technology in Indonesia led to the acts No 19, 2012 about copy right. The law of copy right basically had accommodated the development of technology in Indonesia but law enforcement for the cases in digital technology basis was important element. The state’s responsibility was to give protection towards the copy right based on the government law. The law should also be implemented precisely, to make sure that the developed digital technology did not ruin basic principle of copy right